Icariin protects rats against 5/6 nephrectomy-induced chronic kidney failure by increasing the number of renal stem cells. Issue 1 (December 2015) - Huang, Zhongdi; He, Liqun; Huang, Di; Lei, Shi; Gao, Jiandong
Abstract Background Chronic kidney disease poses a serious health problem worldwide with increasing prevalence and lack of effective treatment. This study aimed to investigate the mechanism of icariin in alleviating chronic renal failure induced by 5/6 nephrectomy in rats. Methods The chronic renal failure model was established by a two-phased 5/6 nephrectomy procedure. The model rats were given daily doses of water or icariin for 8 weeks. The kidney morphology was checked by HE staining. The levels of blood urea nitrogen, serum creatinine, and serum uric acid were measured by colometric methods. The expression of specified genes was analyzed by quantitative real-time PCR and immunohistochemical staining. The number of renal stem/progenitor cells was analyzed by CD133 and CD24 immunohistochemical staining. Results Icariin protected against CDK-caused damages to kidney histology and improved renal function, significantly reduced levels of BUN, creatinine, and uric acid. Icariin inhibited the expression level of TGF-β1 whereas upregulated HGF, BMP-7, WT-1, and Pax2 expression. Moreover, ccariin significantly increased the expression of CD24, CD133, Osr1, and Nanog in remnant kidney and the numbers of CD133+ /CD24+ renal stem/progenitor cells. Conclusions These data demonstrated that icariin effectively alleviated 5/6 nephrectomy induced chronic renal failure through increasing renal stem/progenitor cells.